Distribución, abundancia y reproducción de Opisthonema oglinum (Pisces: Clupeidae) en la plataforma continental del sur del Golfo de México - García-Abad, M C (1998)
Al present the ecological understanding and evaluation of tropical demersal fish cornmunities have their bases on studies about the biology and ecology of dominan! species. The Campeche Sound, in the southem Gulf of Mexico, has more than 300 species in ¡he demersal fish community and 30 are dominants. Among these speeies, Opisthonema oglinum is dominant by its frequency, distribution and abundance. This work determined the panem of abundance and distribution of o. oglinum, and its reproduction, maturity and recruitment. Fish were collected with a shrimp trawl net during six oceanographic cruises in ¡he Campeche Sound. The cruises correspond with the three characteristic seasons in the area: rain y, "nortes", and dry season. A total of 813 individual s with sizes between 56 and 205 mm of total length were eolleeted; they weighted 30 211.5 g. O. oglinum is a typical pelagic-neritie speeies, and is estuarine dependent. This speeies occurs in the inner shelf waters of the Campeche Sound, less. than 36 m deep and mainly in areas influenced by coastal discharges. It also oceurs in the Terminos Lagoon (southern Campeche Sound) and oceasionally in the riverine systems that drain ¡nto the lagoon. The highest biomass and density are on depths !esser than 20 m, in June and August-October. The high density of juveniles mainly determines the higher biomass. Maturity can start al a lotal length of 126 mm, but the size of fust maturity is 135 mm of total length. Reproduction oceurs fmm May to October with two evident peaks during May and August in depths greater Ihan 18 m. The juveniles are found in Ihe shelf and inside of the Terminos Lagoon. Recruitment is from June lo October (rainy season). The visceral and gonadie índices showed Ihat the greatest alimentary aetivity is from June lo August and in November. The condition factor is lowest in June, where the recruítmenl is highest, and highest in November, alter spawning.